Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Karakter Disiplin Peserta Didik di MIN 4 Way Jepara Lampung Timur: Penelitian - Umi Fadhilah; Damanhuri; Septiani Selly Susanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the role of Islamic Education teachers in instilling discipline character values in students at MIN 4 Way Jepara, Lampung Timur. The method used is qualitative descriptive, with data collection techniques through interviews, observations, and documentation. The subjects of the research include Islamic Education teachers and students at the school. The results of the study indicate that teachers act as demonstrators, classroom managers, mediators, facilitators, and evaluators in the process of instilling discipline character. The methods applied include exemplary behavior, advice, discussions, and a loving approach. The main challenge faced is the low personal awareness of students who are still in the developmental stage. The instillation of discipline character values has been shown to significantly enhance discipline and shape the moral and spiritual character of the students. This research emphasizes that the role of Islamic Education teachers is crucial in instilling discipline character values, which contributes to the character formation of students at MIN 4 Way Jepara, Lampung Timur.